Real-time simulation of BLDC motors for hardware-in-the-loop applications incorporating sensorless control - Schulte, Thomas; Bracker, J.
This paper presents a hardware-in-the-loop simulation system for simulating BLDC motors. The test bench combines two key technologies; first an electric motor simulation on the electric interface level, which is not only based on control signals but also emulates real currents and voltages; secondly an FPGA-based (field-programmable gate array) electric motor model. The overall simulation concept represents a comprehensive simulation of the electric motor, which is therefore suitable for running controllers incorporating sensorless motor control. Thus it enables integrated hardware-in-the-loop testing for control units which could formerly only be tested by means of mechanical test benches.